Broken sewing needle in the middle finger; a sewing mishap: Management - Verma, Mukta; Singh, Arun K; Singh, Manish (Indian Journal of Case Reports, 2018)
Accidental penetrating injuries to the finger are common and their improper assessment can result in missed foreign bodies. Thesecan result in a wide range of complications. Removal of retained foreign bodies is really challenging. We report the case of amale tailor who came to the department with a chief complaint of accidental injury with sewing machine needle and the brokenpiece of needle got stuck in his finger. This case report highlights the management of deeply embedded broken needle without theuse of any expensive investigation. Even preoperative plain X-ray with a radio-opaque marker can localize the missed radio-opaqueforeign body accurately. A comprehensive approach results in a successful removal of the foreign body and improved quality of life.